The Gothic Imagination - Tibbetts, John C. author. aut Link
XV, 422 p. 64 illus.
Keywords: This book brings together the author's interviews with many prominent figures in fantasy, horror, and science fiction to examine the traditions and extensions of the gothic mode of storytelling over the last 200 years and its contemporary influence on film and media. .